2014
DOI: 10.1017/jtp.2014.11
|View full text |Cite
|
Sign up to set email alerts
|

We believe in your conspiracy if we distrust you: the role of intergroup distrust in structuring the effect of Islamic identification, competitive victimhood, and group incompatibility on belief in a conspiracy theory

Abstract: Link to this article: http://journals.cambridge.org/abstract_S1838990214000118How to cite this article: Ali Mashuri and Esti Zaduqisti (2014). We believe in your conspiracy if we distrust you: the role of intergroup distrust in structuring the effect of Islamic identication, competitive victimhood, and group incompatibility on belief in a conspiracy This study examined how distrust towards an out-group believed to be an actor of a conspiracy theory moderates the role of Islamic identification, group incompati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
2
16
0
1
Order By: Relevance
“…However, we contend that Muslims are prone to categorize radical Islamists as their ingroup whereas the West as outgroup, despite the fact that they are very moderate and hence lowly identify with radical Islamists. The reason is that Muslims, more specifically Muslims in Indonesia, regardless of their religious orientations, are vulnerable to malevolent conspiracy theories portraying that the West is suspected of engineering and masterminding domestic or even international terrorism ( Bowen, 2007 ; Jones, 2002 , 2009 ; Mashuri & Zaduqisti, 2014a , 2014b ; Perlez, 2002 ; Smith, 2005 ). This type of negative thinking in part stems from an array of perceived deprivations such as injustice, defeat, and powerlessness Muslims subjectively experience in their relations with the West ( Suciu, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we contend that Muslims are prone to categorize radical Islamists as their ingroup whereas the West as outgroup, despite the fact that they are very moderate and hence lowly identify with radical Islamists. The reason is that Muslims, more specifically Muslims in Indonesia, regardless of their religious orientations, are vulnerable to malevolent conspiracy theories portraying that the West is suspected of engineering and masterminding domestic or even international terrorism ( Bowen, 2007 ; Jones, 2002 , 2009 ; Mashuri & Zaduqisti, 2014a , 2014b ; Perlez, 2002 ; Smith, 2005 ). This type of negative thinking in part stems from an array of perceived deprivations such as injustice, defeat, and powerlessness Muslims subjectively experience in their relations with the West ( Suciu, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indonesian authorities have made much effort to crack down on terrorist groups by detaining and even killing some members and suspected members of these groups, as well as disseminating information that these radical groups are the real perpetrators of the terrorism ( Perdani & Parlina, 2014 ). However, it is believed that much of the Indonesian public has disregarded such official reports and even otherwise externalizes the problem by blaming the West as having created terrorism in Indonesia ( Jones, 2009 ; Mashuri & Zaduqisti, 2014a , 2014b ). The West in this discourse is believed to be the real terrorists whereas Indonesian radical Islamists are just their puppets ( Hilmy, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…A conviction that others conspire against one’s group is more likely to emerge when the group thinks of itself as undervalued, underprivileged, or under threat (Uscinski & Parent, ). For example, research by Mashuri and Zaduqisti () demonstrated that beliefs that Western people have victimized Muslims were associated with belief in conspiracy theories suggesting that Western intelligence services instigated terrorism in Indonesia. Bilewicz, Winiewski, Kofta, and Wojcik () showed similar findings in a Polish sample with respect to conspiracy theories about Jews.…”
Section: Definitionsmentioning
confidence: 99%
“…Situational threats and crisis situations can also increase the likelihood of strong group attachment to foster conspiracy beliefs (Kofta, Sędek, & Sławuta, ; Mashuri & Zaduqisti, ; van Prooijen & Douglas, ; Thomson et al, 2012). Taken together, findings from research on the role of social identification highlight the fact that feelings of being undermined and threatened in the context of international relations can facilitate the development of conspiracy theories that serve to justify groups’ disadvantaged position (Uscinski & Parent, ).…”
Section: Definitionsmentioning
confidence: 99%
“… 2013 ; Douglas et al. 2019 ; Goertzel 1994 ; Mashuri and Zaduqisti 2014 ; Miller et al. 2016 ; Parsons et al.…”
Section: A Model Of Misinfodemic By Paranoid Agentsunclassified